Towards a legal theory of capture. Issue 6 (1st May 2018) - Devaux, Caroline
Abstract: To assert their role in global governance, international organisations, including the EU, have progressively involved economic actors in their activities, particularly in the course of law‐making processes. Their integration, even if necessary, raises the risk of excessive influence that they may exert on law‐makers. The paper builds on the theory of regulation that coined the concept of 'capture' and proposes to analyse the conditions and effects of such phenomenon within three selected international organisations that are particularly prone to the influence of economic actors: the United Nations (UN), the International Institute for the Unification of Private Law (UNIDROIT) and the International Centre for Settlement of Investment Disputes (ICSID). In light of their practice, the paper suggests key features that an EU legal framework could take to promote the participation of economic actors in its law‐making process while preventing the occurrence of capture.